(untitled) (Research, Society and Development, 2020)
Objective: to evaluate a safety culture in a university surgical center, checking if there is a difference in assessment between the support, nursing and medical teams. Methods: cross-sectional, descriptive, quantitative study, performed in the operating room of a university hospital, with health professionals between March and June 2019, using the Safety Attitudes Questionnaire/Operating Room as an instrument. Descriptive and inferential statistical analysis was performed. Results: the global score was 59.45%, the support team had three positive domains, perceived stress 78.88%, work condition 77.86% and safety climate 76.06%, followed the nursing team in the communication domain 75,11% and the medical team didn’t present any positive domain. The surgical center teams showed three significant differences between the safety culture domains. Conclusion: the results allowed to evaluate the safety culture of the university surgical center and the differences between the teams, contributing to the improvement of surgical assistance.